Isu Kafir-mengkafir Dan Implikasinya dalam Perkembangan Politik dan Sosial Masyarakat Melayu - Hj Abd. Latiff, Ahmad Zaki (Jurnal Usuluddin, 2003)
This article attempts to explain the origin of the word 'takfir' as stated in the Qur'an and how it is related to the act of infidel accusation which arose within the Islamic society resulting from the existence of 'al-khawarij' and 'al-takflr wa al-hijrah' sects. The ulama prohibit the act of 'infidel accusation' among the ummah since it involves the 'aqidah', which instigates disunity. In the history of Malay society, the "infidel accusation ", which has caused social, political and "dakwah " disunity, is normally associated with extreme approaches in pursuing political and religious objectives. The article suggests a moderate approach based on Islamic dakwah formula as adopted by some famous Islamic scholars such as Hasan al-Banna, Yusuf' al-Qaradawi and Abu Hassan 'Ali al-Nadwi to maintain Muslim unity.